2020
DOI: 10.1097/apo.0000000000000263
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Positive Microbial Culture in Patients With Endophthalmitis Based on Clinical Presentation and Multimodal Intraocular Sampling

Abstract: Purpose: The aim of this study was to identify the factors associated with positive culture sample in patients with endophthalmitis based on clinical presentation and multimodal intraocular sampling. Design: Retrospective review. Methods: A total of 259 subjects with a diagnosis of endophthalmitis presented to a tertiary ophthalmic referral center between 2006 and 2018. Patient demographics, presenting clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Moreover, whether a sample is positively-cultured is related to many factors, such as the clinical characteristics of the patient, the sampling sites as well as laboratory facilities. Studies indicate that both aqueous tap and vitrectomy can increase the possibility of obtaining a positive culture [26] . Culture media also poses influences to culture results [27][28][29] .…”
Section: Traditional Laboratory Diagnosis Of Endophthalmitismentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, whether a sample is positively-cultured is related to many factors, such as the clinical characteristics of the patient, the sampling sites as well as laboratory facilities. Studies indicate that both aqueous tap and vitrectomy can increase the possibility of obtaining a positive culture [26] . Culture media also poses influences to culture results [27][28][29] .…”
Section: Traditional Laboratory Diagnosis Of Endophthalmitismentioning
confidence: 99%
“…Culture media also poses influences to culture results [27][28][29] . We summarized the sequencing and culture results of clinically suspected endophthalmitis in Table 1 [4,20,23,26, . Due to the low and varied culture rate and the small amount of intraocular fluid samples, rapid and accurate diagnosis of acute endophthalmitis is very important and closely related to the degree of visual loss of the patient.…”
Section: Traditional Laboratory Diagnosis Of Endophthalmitismentioning
confidence: 99%
“…However, the culture technique can only isolate specific microorganisms that meet the conditions of the Petri dish, which fails to show the overall composition of the microbial community ( Table 3 ). Moreover, culture techniques typically require several weeks or more to provide conclusive results, and the rate of positive results is low [ 15 ], requiring the aid of other pathogen detection methods.…”
Section: Discussionmentioning
confidence: 99%
“…Even if the patient has been clinically cured, the etiology remains unclear, which necessitates the identification of the causative agent of infection. The microbiological diagnosis by microbial culture technology has made outstanding contributions to infectious eye diseases, not only by culturing pathogenic microorganisms but also by evaluating their drug sensitivity [ 15 ]. It is considered the “gold standard” for diagnosing infectious ocular diseases [ 16 ].…”
Section: Traditional Diagnostic Methods To Determine the Cause Of Ocu...mentioning
confidence: 99%
“…The reported culture positivity vary widely. In a prospective multi-centric study from USA the endophthalmitis vitrectomy study group (EVS) reported 69% culture positivity ( Barza et al., 1997 ); a study from New Zealand reported 51% culture positivity ( Bhikoo et al., 2020 ). However in countries where antibiotic use is very common and indiscriminate, most patients had already received antibiotics prior to hospital visit which may result in low culture positivity.…”
Section: Introductionmentioning
confidence: 99%